Topochemical cation exchange reactions of Ruddlesden-Popper oxides - Conway, R (2024)
The work detailed in this thesis focuses on the low-temperature, topochemical cation exchange reactions of a series of some noncentrosymmetric n = 2 pseudo-Ruddlesden-Popper oxides.